2019
DOI: 10.1016/j.invent.2018.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Guided internet-based transdiagnostic intervention for Indonesian university students with symptoms of anxiety and depression: A pilot study protocol

Abstract: BackgroundThere is an increasing prevalence of mental health problems among university student populations. In Indonesia, treatment rates are low among university students because of the high cost of treatment, stigma and the limited availability of mental care services. Internet-based interventions have been found to be effective in treating anxiety and depression in Western countries. However, little is known about the effectiveness of Internet-based interventions in low- and middle-income countries (LMICs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 55 publications
1
24
0
Order By: Relevance
“…[ 19 ] It consists of 9 items derived from diagnostic and statistical manual of mental disorders (DSM-IV). [ 20 ] Participants are asked to consider over the last 2 weeks, how often they have been bothered by a list of nine problems, for example, “Little interest or pleasure in doing things”. Items are scored against a Likert scale ranging from 0 (Not at all) to 3 (Nearly every day) with summed total scores ranging from 0 to 27.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 19 ] It consists of 9 items derived from diagnostic and statistical manual of mental disorders (DSM-IV). [ 20 ] Participants are asked to consider over the last 2 weeks, how often they have been bothered by a list of nine problems, for example, “Little interest or pleasure in doing things”. Items are scored against a Likert scale ranging from 0 (Not at all) to 3 (Nearly every day) with summed total scores ranging from 0 to 27.…”
Section: Methodsmentioning
confidence: 99%
“…GAD-7 a 7-item scale designed to assess symptoms of anxiety [ 20 ]. Participants are asked to how frequently over past two weeks they have been bothered by list of seven problems such as for example, “Feeling nervous, anxious, or on edge” [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…This paper reports the results of stage 3 from a theory-based cultural adaption framework, namely, preliminary adaptation test [ 32 ]. The first 2 stages of the framework, namely, information gathering and preliminary adaptation design, are reported in the protocol paper of this study [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Digital mental health interventions are promising intervention programs to address the mental health burden in contexts where there are few mental health providers [ 14 ]. For example, a randomized controlled trial in Indonesia demonstrated that a guided self-help intervention reduced depression symptoms [ 15 ].…”
Section: Introductionmentioning
confidence: 99%